Current status and future tends of combined process for producing acetone and phenol. II. Intensification methods of cumene oxidation process - L. B. Larin; E. V. Egorova; E. A. Ananieva (Тонкие химические технологии)
The application of ozone as initiator of cumene oxidation is shown to result in feed conversion increased to 28%, with selectivity closed to 100%, instead of accordingly 21% and 88% in method using cumene hydroperoxide as initiator. Optimal conditions for cumene oxidation are determined.